Answer :

Given: L.H.S. =


Since we know


So L.H.S.
=
=

Multiplying Numerator & Denominator with sin θ - (1 - cos θ) we get

L.H.S.

=


Since sin2 θ + cos2 θ = 1


Taking 2 common out of numerator and denominator 

=



L.H.S. = R.H.S.


Hence Proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Heights and Distances-IHeights and Distances-IHeights and Distances-I45 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses